2014 22nd International Conference on Pattern Recognition 2014
DOI: 10.1109/icpr.2014.685
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Optical Flow Model for Scattering Media

Abstract: This paper proposes a novel methodology to estimate the optical flow in scattering media, which consists on new formulation based on the classical Horn-Schunk approach and the optical image formation model. Our formulation is able to deal with the hard problem of tracking points in a medium where there is absorption and scattering effects. This approach generalizes assumptions of the Horn-Schunk model in order to tackle both non-scattering and scattering media. Our approach uses the Dark Channel Prior to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Correspondingly, a simplified digital image model is developed to represent the process of obtaining the displacement measurements from images (a "measurement model") using the optical flow method. Given the fact that Drews et al (2014) found turbidity increases the error of optical flow fields and Madjidi and Negahdaripour (2006) proved that the low-contrast photo underestimates the magnitude of the optical flow field, the model down-sizes the displacement measurements and assigns a noise that represents the noise level of photos taken underwater. This noise also accounts for environmental factors such as camera vibration and light source movement over a lock filling event.…”
Section: Image Monitoring Datamentioning
confidence: 99%
“…Correspondingly, a simplified digital image model is developed to represent the process of obtaining the displacement measurements from images (a "measurement model") using the optical flow method. Given the fact that Drews et al (2014) found turbidity increases the error of optical flow fields and Madjidi and Negahdaripour (2006) proved that the low-contrast photo underestimates the magnitude of the optical flow field, the model down-sizes the displacement measurements and assigns a noise that represents the noise level of photos taken underwater. This noise also accounts for environmental factors such as camera vibration and light source movement over a lock filling event.…”
Section: Image Monitoring Datamentioning
confidence: 99%